Studying the preservation of Brussels sprout depending on its treatment with antimicrobial preparations before storage - Pusik, Ludmila; Pusik Vlаdimir; Bondarenko, Veronika; Gaevaya, Ludmila; Kyruchina, Natalja; Slobodyanyk, Halyna; Shchetyna, Serhii; Shchetyna, Maryna; Kononenko, Lidiia (Eastern-European Journal of Enterprise Technologies, 2020)
The effect of antimicrobial preparations on the intensity of losses in the quality of Brussels sprout heads during storage has been scientifically substantiated. Brussels sprout heads were treated with antimicrobial solutions before storage. The following solutions were used: 0.05 % sorbic acid, 0.2 % benzoic, 0.5 % citric acid, Baikal EM-1, 0.5 % solution of ascorutin. The heads were stored in boxes lined with a 40 µm thick polyethylene film. Treatment with antimicrobial preparations increases the shelf life of Brussels sprout to 50 days without significant weight loss. A solution of sorbic acid significantly reduces the natural mass loss by Brussels sprout after 10 days of storage. The effect of other preparations is observed only on day 30 of storage. Standard product output is 85.2–86.9 % depending on the features of the hybrid. Antimicrobial preparations contribute to the preservation of chemical components in Brussels sprout heads. At the end of storage, the content of dry matter, dry soluble substances, total sugar, and ascorbic acid is 5‒8 % higher than that in the control variant. A greater content of some components of the chemical composition is observed in produce treated with solutions of sorbic and benzoic acids before storage. Solutions of sorbic and benzoic acids effectively hinder the development of harmful microorganisms on the heads of Brussels sprout. The result of this study has established that a 0.05 % solution of sorbic acid and a 0.2 % solution of benzoic acid are more effective at contributing to the preservation of quality by Brussels sprout heads. Sorbic and benzoic acids do not affect the organoleptic properties of products and are safe for humans. This makes it possible to recommend to use their solutions as an effective and safe measure to preserve the quality of vegetable produce over its long-term storage